2020
DOI: 10.1002/esp.4839
|View full text |Cite
|
Sign up to set email alerts
|

Seabed erosion and deposition related to the typhoon activity of the past millennium on the southeast coast of China

Abstract: Catastrophic events often interrupt long‐term Earth surface processes. In coastal areas, although millennial‐scale trends of climatic and sea‐level changes determine the trajectory of sedimentary landform evolution, storm and/or tsunami activity can cause abrupt changes in depositional conditions that may alter the long‐term sedimentary processes. Here, we report a sedimentary hiatus that is widely observed from the late Holocene sedimentary sequence at the seabed along the southeast China coast. This hiatus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…Due to the disturbed sediments found in both cores of the same lagoon, Yue et al (2019) inferred possible tsunami-induced events. However, distinguishing typhoon and tsunami deposits is very difficult, therefore we cannot confirm the tsunami occurrence recorded in Layer 6 (Xiong et al, 2020). The confirmation of tsunami needs further studies on land, as the differentiation criteria (e.g.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Due to the disturbed sediments found in both cores of the same lagoon, Yue et al (2019) inferred possible tsunami-induced events. However, distinguishing typhoon and tsunami deposits is very difficult, therefore we cannot confirm the tsunami occurrence recorded in Layer 6 (Xiong et al, 2020). The confirmation of tsunami needs further studies on land, as the differentiation criteria (e.g.…”
Section: Discussionmentioning
confidence: 86%
“…This is supported by previous studies. For instance, due to the huge typhoons in history, the seabed erosion occurred for the cores out of the PRE, which results in the post-eroded deposits filled with shell fragments and coarsened fractions (Xiong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (e.g., Ramos et al., 2017; Sun et al., 2013; Yang et al., 2019) have suggested that one paleo‐tsunami affected the central to northern parts of the SCS around AD 1000, and the earthquake was originated from the Manila Trench (Lau et al., 2010; Mak & Chan, 2007; Ramos et al., 2017; Sun et al., 2013; Xiong et al., 2020). On the other hand, some other studies (Goff et al., 2020; Qiu et al., 2019) suspected that no paleo‐tsunami affected the SCS in the past millennium, and no sedimentary evidence of paleo‐tsunami event affecting the Xisha Islands area has been recorded since that time (Sun et al., 2013; Yan et al., 2011; Yue et al., 2019).…”
Section: Resultsmentioning
confidence: 98%
“…The historical documentary record in the Hainan and parts of Guangdong (Chu et al., 2002); 7 . HKUV10 (Xiong et al., 2020); 8. The historical documentary record of Hainan and Guangdong (Liu et al., 2001); 9.…”
Section: Introductionmentioning
confidence: 99%